A Proposed Hybrid Blockchain-DID-ZKP Approach to Secure, Auditable, and Private Healthcare Interoperability - Sahil Fruitwala; Purva Desai (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
Traditionally, health records are kept in siloed data storages of different health organizations. Today, all patients’ EHRs (Electronic Health Records) are used and shared with different institutes and research facilities without their consent. To protect and overcome pitfalls of generic systems, we introduce a new hybrid system called Hybrid Patient Data Vault (HPDV). This hybrid system can help patients securely share their health information in a manner that could allow them to share only what is necessary or in need-to-know basis. We detail the system’s components, workflows, and emergency protocols, emphasizing patient-centric design. Through a STRIDE-based threat model and simulations of key metrics like transaction latency and ZKP generation time, we demonstrate HPDV’s security and feasibility. Our evaluation shows it outperforms monolithic approaches in auditability and privacy, with ZKP proofs generated in under 7 seconds on standard devices. This work demonstrates a practical modern approach for secure, patient-controlled health data exchange.